2004
DOI: 10.1111/j.0306-686x.2004.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Intraday Patterns of Initial Public Offerings: Evidence from Hong Kong

Abstract: This paper examines the intraday patterns of IPOs in Hong Kong during the period 1995-1998. The results reveal that the well-known under-pricing phenomenon of IPOs occurs only at the opening trading of new issues and vanishes afterwards. The return volatility of IPOs is found to be high during the first trading session, and declines rapidly during the rest of the first trading day until the end of the trading day. The intraday return volatility of IPOs is found to follow a double U-shape pattern, which is simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
2
4
0
1
Order By: Relevance
“…When compared with other Asian countries, initial returns observed in Hong Kong IPOs during recent periods are modest. Moreover, when results reported by Dawson and Hiraki (1985), Dawson (1987), McGuinness (1992, Chen et al (2001), Cheng et al (2004), Cheng et al (2006), Vong (2006), Vong and Zhao (2008) and others, are compared with those obtained in the present paper, it is concluded that underpricing in Hong Kong has experienced a significant decrease from the year of 2001 on.…”
Section: Introductionsupporting
confidence: 65%
“…When compared with other Asian countries, initial returns observed in Hong Kong IPOs during recent periods are modest. Moreover, when results reported by Dawson and Hiraki (1985), Dawson (1987), McGuinness (1992, Chen et al (2001), Cheng et al (2004), Cheng et al (2006), Vong (2006), Vong and Zhao (2008) and others, are compared with those obtained in the present paper, it is concluded that underpricing in Hong Kong has experienced a significant decrease from the year of 2001 on.…”
Section: Introductionsupporting
confidence: 65%
“…Bora et al (2012) reported that Indian IPOs are underpriced when measured using offer price and the opening price on listing day (which is again consistent with our measure using the same prices). Also, Cheung and Krinsky (1994) and Cheng et al (2004) documented underpricing using similar measure. Both of these studies found that underpricing is significant when computed using offer-to-open measure.…”
Section: Discussionmentioning
confidence: 80%
“…IPOs from developed countries are more underpriced and privatisation of IPOs are less underpriced than nonprivatisations. Examining the intraday patterns of IPOs in Hong Kong, Cheng, Cheung, and Po (2004) found that underpricing of IPOs occurs only at the pre-listing market and disappears afterwards i.e. Hong Kong market is efficient in adjusting for IPO underpricing.…”
Section: Listing Day Underpricingmentioning
confidence: 99%
“…Previous IPO studies on Hong Kong such asMcGuinness (1992) find that there exists 17.6 percent initial underpricing of the IPO firms. WhenCheng, Cheung and Po (2004) split their sample into pre-and post-1997 Asian Financial…”
mentioning
confidence: 99%